THE EFFECT OF NET PROFIT, ACCOUNT PAYABLE, CASH TURNOVER AND INVENTORY TURNOVER ON OPERATIONAL CASH FLOW IN PT. MULIA - Henny Permata Sari; Sunarji Harahap; Elidawati Elidawati; Thomas Sumarsan Goh (Magister Akuntansi, Universitas Atma Jaya Makassar, 2022)
The company's financial statements are the final result of accounting activities (accounting cycle) that reflect the financial condition and results of the company's financial operations. are outside (external) the company. Therefore, financial statements can be used as a tool to communicate with the parties with the company's financial data (The dan Sugiono, 2015). Users of financial information include: investors, employees, creditors, suppliers, governments and the general public. The company's published financial statements are an important source of information for investors and creditors to be able to analyze the work of management in making profits and cash flows in the future (Simangunsong, et al, 2018). Users of financial statements such as investors and creditors are more interested in what will happen in the future. The company's performance parameters of concern are the components of cash flow and profit. The cash flow statement is one type of financial statement that has the entity's ability to generate cash flows in the future, the cash flow statement can be used as a tool to predict the company's future cash flows. Analysis of research data used in this study is multiple linear regression analysis model. Primary data were collected and obtained through observational interviews, documentation studies and literature studies, while secondary data were obtained from literature related to the research topic. The financial statements used as the object of research. The results showed that Net Profit had no effect on the Operating Cash Flow of PT. Mulia, Accounts Payable has a significant effect on the Operational Cash Flow of PT. Mulia, Cash Turnover has a significant effect on the Operational Cash Flow of PT. Mulia, Inventory Turnover has no effect on the Operational Cash Flow of PT. Mulia Mulia Abadi and Net Profit, Accounts Payable, Cash Turnover and Inventory Turnover have a significant effect on the Operational Cash Flow of PT. Mulia.